﻿ Solve 3x^3+1=0 | Uniteasy.com

# Solve the cubic equation:

## $$3x^3+1=0$$

Since the discriminant $$\Delta >0$$, the cubic equation has one real root and two conjugate complex roots.

$$\Delta=0.027777777777778$$

$$\begin{cases} x_1=-\sqrt{\dfrac{1}{3}} \\ x_2=\dfrac{1}{2}\sqrt{\dfrac{1}{3}}+\dfrac{1}{2}\sqrt{\dfrac{1}{3}}\sqrt{3}i \\ x_3=\dfrac{1}{2}\sqrt{\dfrac{1}{3}}-\dfrac{1}{2}\sqrt{\dfrac{1}{3}}\sqrt{3}i \end{cases}$$

In decimals,

$$\begin{cases} x_1=-0.69336127435063 \\ x_2=0.5+0.86602540378444i \\ x_3=0.5-0.86602540378444i \end{cases}$$

Detailed Steps on Solution

## 1. Use the sum of cubes identity

This cubic equation $$3x³ + 1=0$$ contains only a cubic term and a constant term. It might be the simplest form of a cubic equation.

To simplify, divide both sides of the equation by $$3$$ so that the coefficient of the leading term is equat to $$1$$.

$$x^3+\dfrac{1}{3} = 0$$

Isolate the leading term by moving the constant term to the right hand side.

$$x^3 = -\dfrac{1}{3}$$

and then take cubic roots on the both sides, which results in

$$x =\sqrt{\dfrac{1}{3}}$$

If the solution is to find only real root, that's all. However, if it is to find all solutions, need more steps since a cubic eqaution normally has three roots.(Some may have duplicate ones)

### Factorization by sum of cubes identity

To find complete roots, use the sum of cubes formula to factorize the binomial

$$\Big(x+\sqrt{\dfrac{1}{3}}\Big)\Big[(x)^2-x\cdot \sqrt{\dfrac{1}{3}}+(\sqrt{\dfrac{1}{3}})^2\Big] = 0$$

Now the binomial on the left hand side is transformed to a product of two expressions. If the above equation is to hold true, either of the expressions is equal to zero.

Then we get a linear equation

$$x+\sqrt{\dfrac{1}{3}}=0$$

$$(x)^2-x\cdot \sqrt{\dfrac{1}{3}}+(\sqrt{\dfrac{1}{3}})^2=0$$

### Solve the linear equation $$x+\sqrt{\dfrac{1}{3}}=0$$

Subtract the value of the constant term from both sides yields the first solution.

$$x_1=-\sqrt{\dfrac{1}{3}}\approx-0.69336127435063$$

### Solve the quadratic equation $$(x)^2-x\cdot \sqrt{\dfrac{1}{3}}+(\sqrt{\dfrac{1}{3}})^2$$

Let $$m = -\sqrt{\dfrac{1}{3}}$$, then the equation is simplified as

$$x^2+mx+m^2= 0$$

Using the root identity for a quadratic equation, $$x$$ is found to be the product of $$m$$ and a complex number.

\begin{aligned}\\ x&=\dfrac{-b\pm\sqrt{b^2-4ac} }{2a} \\ &=\dfrac{-m\pm m\sqrt{3}i}{2} \\ \end{aligned}

Substitute the value of $$m$$, that is, $$m=-\sqrt{\dfrac{1}{3}}$$, then we get another two complex roots

$$x_2 =\dfrac{1}{2}\sqrt{\dfrac{1}{3}}\Big(1+ \sqrt{3}i\Big)$$

$$x_3 =\dfrac{1}{2}\sqrt{\dfrac{1}{3}}\Big(1- \sqrt{3}i\Big)$$

## 2. Cubic Root Formula

The equation $$3x³ + 1=0$$ has no quadratic term, compared with the general cubic equation. We can use the root formula to calculate the roots direvtly.

$$t^3 +pt+q=0$$

For the equation , we have $$p=0$$ and $$q = \dfrac{1}{3}$$

### Calculate the discriminant

The nature of the roots are determined by the sign of the discriminant.

\begin{aligned} \\\Delta&=\dfrac{q^2}{4}+\dfrac{p^3}{27}\\ & =\dfrac{\Big(\dfrac{1}{3}\Big)^2}{4}+0\\ & =\dfrac{1}{36}\\ & =0.027777777777778\\ \end{aligned}

### 2.1 Use the root formula directly

If the discriminant is greater than zero, we can use the root formula to determine the roots of the cubic equation.

$$t_{1,2,3} =\begin{cases} \sqrt{-\dfrac{q}{2}+\sqrt{\dfrac{q^2}{4}+\dfrac{p^3}{27} } } +\sqrt{-\dfrac{q}{2} -\sqrt{\dfrac{q^2}{4}+\dfrac{p^3}{27} }}& \\ ω\cdotp \sqrt{-\dfrac{q}{2}+\sqrt{\dfrac{q^2}{4}+\dfrac{p^3}{27} } } + \overline{ω} \sqrt{-\dfrac{q}{2} -\sqrt{\dfrac{q^2}{4}+\dfrac{p^3}{27} }}&\ \\ \overline{ω}\cdotp \sqrt{-\dfrac{q}{2}+\sqrt{\dfrac{q^2}{4}+\dfrac{p^3}{27} } } + ω\cdotp \sqrt{-\dfrac{q}{2} -\sqrt{\dfrac{q^2}{4}+\dfrac{p^3}{27} }} \end{cases}$$

in which, $$ω = \dfrac{-1+i\sqrt{3}}{2}$$ and $$\overline{ω} =\dfrac{-1-i\sqrt{3}}{2}$$

Substitute the values of $$p, q$$ and $$\Delta$$ which we have calculated. Then,

\begin{aligned} \\t_1&=\sqrt{-\dfrac{1}{6}+\sqrt{\dfrac{1}{36}}}+\sqrt{-\dfrac{1}{6}-\sqrt{\dfrac{1}{36}}}\\ & =\sqrt{-\dfrac{1}{6}+\dfrac{1}{6}}+\sqrt{-\dfrac{1}{6}-\dfrac{1}{6}}\\ & =-\sqrt{\dfrac{1}{3}}\\ \end{aligned}

If we denote

$$R = -\dfrac{q}{2}+\sqrt{\dfrac{q^2}{4}+\dfrac{p^3}{27} }$$

$$\overline{R} = -\dfrac{q}{2} -\sqrt{\dfrac{q^2}{4}+\dfrac{p^3}{27} }$$

then,

$$\sqrt{R} = 0$$, $$\sqrt{\overline{R}} =-\sqrt{\dfrac{1}{3}}$$

\begin{aligned} \\t_2&= ω\cdotp \sqrt{R}+ \overline{ω} \sqrt{\overline{R} }\\ & =\dfrac{-\sqrt{R}-\sqrt{\overline{R} }}{2} +\dfrac{\sqrt{3}( \sqrt{R} - \sqrt{\overline{R} }) }{2} i\\ & =\dfrac{1}{2}\Big[0-\Big(-\sqrt{\dfrac{1}{3}}\Big)\Big]+\dfrac{\sqrt{3}}{2}\Big[0-\Big(-\sqrt{\dfrac{1}{3}}\Big)\Big]i\\ & =\dfrac{1}{2}\sqrt{\dfrac{1}{3}}+\dfrac{1}{2}\sqrt{\dfrac{1}{3}}\sqrt{3}i\\ \end{aligned}

\begin{aligned} \\t_3&= \overline{ω}\cdotp \sqrt{R}+ ω\cdotp \sqrt{\overline{R}}\\ & =\dfrac{-\sqrt{R}-\sqrt{\overline{R} }}{2} +\dfrac{\sqrt{3}(- \sqrt{R} + \sqrt{\overline{R} }) }{2}i \\ & =\dfrac{1}{2}\Big[0-\Big(-\sqrt{\dfrac{1}{3}}\Big)\Big]-\dfrac{\sqrt{3}}{2}\Big[0-\Big(-\sqrt{\dfrac{1}{3}}\Big)\Big]i\\ & =\dfrac{1}{2}\sqrt{\dfrac{1}{3}}-\dfrac{1}{2}\sqrt{\dfrac{1}{3}}\sqrt{3}i\\ \end{aligned}

## 3. Summary

In summary, we have tried the method of to explore the solutions of the equation. The cubic equation $$3x³ + 1=0$$ is found to have one real root and two complex roots. Exact values and approximations are given below.

$$\begin{cases} x_1=-\sqrt{\dfrac{1}{3}} \\ x_2=\dfrac{1}{2}\sqrt{\dfrac{1}{3}}+\dfrac{1}{2}\sqrt{\dfrac{1}{3}}\sqrt{3}i \\ x_3=\dfrac{1}{2}\sqrt{\dfrac{1}{3}}-\dfrac{1}{2}\sqrt{\dfrac{1}{3}}\sqrt{3}i \end{cases}$$

in decimal notation,

$$\begin{cases} x_1=-0.69336127435063 \\ x_2=0.5+0.86602540378444i \\ x_3=0.5-0.86602540378444i \end{cases}$$

## 4. Graph for the function $$f(x) = 3x³ + 1$$

Since the discriminat is greater than zero, the curve of the cubic function $$f(x) = 3x³ + 1$$ has one intersection point with the x-axis.

Scroll to Top